Some Monetary Aspects of Multiplier Theory and Fiscal Policy - Ritter, Lawrence S. (Review of Economic Studies, 1955)
Journal Article Some Monetary Aspects of Multiplier Theory and Fiscal Policy Get access Lawrence S. Ritter Lawrence S. Ritter Michigan Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 23, Issue 2, 1955, Pages 126–131, https://doi.org/10.2307/2296295 Published: 01 January 1955